Crystalline Perovskite La 0.67-xLi 3x TiO 3: Preparation and Ionic Conducting Characterization - Dinh, Nguyen Nang; Long, Pham Duy; Trong, Le Dinh (Communications in Physics, 2007)
Crystalline perovskite La0.67-xLi 3x TiO 3 with x = 0.06, 0.11 and 0.15 were prepared by solid-state-solution reactions at 1350 0 C from TiO 2 , La 2 O 3 and Li 2 CO 3 Crystalline structure of these compounds was analyzed by XRD method. The ionic conducting property of La 0.67-x Li 3xTiO 3 was characterized on AutoLab. Potentiostat-PGS30 system with impedance technique using fitting software program available in the equipment. The highest ion conductivity at room temperature was found for the compound with x =0.11, namely σ = 3.1 x 10 -5Scm -1. With increase of temperature the ionic conductivity increased and at 2000C it reached a value in two orders in magnitude higher (6 x 10 -3Scm -1). The activation energy of the compounds was determined on Ln(σ) vs. 1/T plots and found to be as low as 0.36 eV.